PENERAPAN ASAS PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) DI KECAMATAN TAROGONG KALER KABUPATEN GARUT PROVINSI JAWA BARAT - Ahmad Ripai (Institut Pemerintahan Dalam Negeri, 2017)
The research about the principles of administrative and integrative public service at district level was taken at Tarogong Kaler District, Garut Regency. It was proposed after the introduction of the regulation from Ministry of Home Affairs Number 4 Year 2010 on the guidance of administrative and integrative service at district level, which was followed by technical guidance for administrative and integrative service at district level. And to narrow the discussion range, I limited the topic on the implementation process of administrative and integrative service at Tarogong Kaler District, Garut Regency. This research is categorized as policy research, which means it is based on the policy that has focused on problem-solving. It also can belong to evaluative research as it aims to evaluate the presence of certain policy and its impact at Tarogong Kaler District in Garut Regency. While for the data source, I employ primer and secondary source from interview, reading lists, and official documents. To begin with, all data is analysed and checked using three criteria, namely: 1) credibility, 2) dependability, and 3) confirmability. To conclude, I claim that Tarogong Kaler District in Garut Regency has implemented the policy based on the Act Number 25 Year 2009 Section 4. For instance, the head of district has established the service standard at Tarogong Kaler District in Garut Regency by running some policies: managing organization, improving the service facilities, finding the best method to run the service, and providing continuous training for all employees so that they gain good knowledge and competencies. Yet, I would like to suggest to expand the internet network and provide more PCs in order to support the application of administrative and integrative public service/PATEN as well as holding more continuous training and short course for public employees so that the Standard Operating Procedure can be applied consistently. Keywords: administrative and integrative public service at district level